Investigation on Polyethylene Terephthalate (PET) Waste Fiber Performances in Concrete Material - Samsudin, Mohamad Aizan; shahiron Shahidan; Abdul Manaf, Adib Fikri; Aznan, Muhammad Fakhri Fahmi; Mohd Zuki, Sharifah Salwa; Ramasamy, Suchitra; Mohammad Azmi, Mohamad Azim (Recent Trends in Civil Engineering and Built Environment, 2021)
Polyethylene Terephthalate (PET) has good properties that can innovate and improve concrete properties. PET is a hard, durable, and waterproof material with excellent thermal and electrical insulation. The goals of this study are to determine the compressive strength and flexural strength of the various percentages of recycled PET fibre (0%, 0.5%, 1.0%, 1.5% and 2.0%) in concrete and to evaluate the optimal percentage of recycled PET fibres in concrete. The PET of this study will be collected from Universiti Tun Hussein Onn Malaysia and residential area at Parit Raja. Straight and irregular recycled PET fibers have been selected for this analysis. The fibers were cut simply from PET bottles. Recycled PET fiber length and width were set at 50 mm and 5 mm, respectively and the percentages are 0.5%, 1.0%, 1.5%, and 2.0% of the PET fibers. Tests have been performed in the form of a slump test, a compressive strength test and a 3-point bending test to assess the mechanical properties and the optimum percentage of PET fibers. All the specimens followed according to British Standard (BS) and conducted in UTHM laboratory. The results shows that by increasing the percentage of PET fibers in concrete, the compressive strength and flexural values also improved. The highest value for compressive strength test was on 1.0% of PET specimen while the highest value for flexural strength test was on 0.5% of PET. Based on the tests conducted in this report, the optimum percentage of recycled PET fibre that can be added to concrete is 1.0 %. For recommendation increase the number of specimens in order to obtain more accurate results.